Threats of Business Environment Performance in Austria and Slovakia - Alexander KELÍŠEK; Jozef KUBÁS; Stanislava STRELCOVÁ; Michal BALLAY (Communications of International Proceedings, 2022)
Quality of the business environment is a key factor for increasing the performance of businesses in a country. The size of the domestic economy is determined by two basic indicators: by the number of inhabitants, or the size of the labour force and the total GDP, or GDP per capita. Other factors of the business environment should be aligned with these two basic indicators. If we want to compare the quality of the business environment in two countries, it is possible to set a comparative coefficient from the basic indicators, which other performance indicators of the business environment should copy. The authors of the article decided to compare the performance of the business environment in Austria and Slovakia. Based on a detailed analysis, they found disproportions in the business environment and formulated conclusions. The reference period for the comparison was the decade of 2009-2018, thus avoiding problematic crisis years during the pandemic of Covid-19.
Keywords: quality of life; performance of business environment; risks; economic growth; disproportions